2020
DOI: 10.2471/blt.20.269142
|View full text |Cite
|
Sign up to set email alerts
|

Government trust, perceptions of COVID-19 and behaviour change: cohort surveys, Singapore

Abstract: Objective To evaluate how public perceptions and trust in government communications affected the adoption of protective behaviour in Singapore during the coronavirus disease 2019 (COVID-19) pandemic. Methods We launched our community-based cohort to assess public perceptions of infectious disease outbreaks in mid-2019. After the first case of COVID-19 was reported in Singapore on 23 January, we launched a series of seven COVID-19 surveys to both existing and regularly enrolled new participants every 2 weeks. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
66
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 83 publications
(72 citation statements)
references
References 16 publications
5
66
0
1
Order By: Relevance
“…Another study was conducted to explore the perception of the public of the government of Singapore in relation to COVID-19 related information. The results of the study confirm that majority of the respondents (99.1%) agreed or strongly agreed on the COVID-19 related information provided by the government and 97.9% believed the Singapore news agency [34]. Another study was carried out in Bangladesh to explore the public perception of government measures related to COVID-19.…”
Section: Comparing the Perceptions Of Migrants With Other Citizenssupporting
confidence: 56%
“…Another study was conducted to explore the perception of the public of the government of Singapore in relation to COVID-19 related information. The results of the study confirm that majority of the respondents (99.1%) agreed or strongly agreed on the COVID-19 related information provided by the government and 97.9% believed the Singapore news agency [34]. Another study was carried out in Bangladesh to explore the public perception of government measures related to COVID-19.…”
Section: Comparing the Perceptions Of Migrants With Other Citizenssupporting
confidence: 56%
“…However, these studies were generally limited by small sample size, data from single country, restricted to early stage of pandemic, and the cross-sectional design. The only longitudinal study is a multi-wave survey of 633 participants in Singapore during January−April 2020 (Lim et al, 2021 ), which showed trust in government communication was positively associated with likelihood of adopting protective behaviour; but that study did not investigate the effect of trust on longitudinal behavioural changes. Moreover, prosocial behaviour has been neglected in previous COVID-19 research, which is important because social support and volunteering could facilitate the prevention and treatment of coronavirus.…”
Section: Introductionmentioning
confidence: 99%
“…Sendo assim, manter a confiança do público nas autoridades de saúde, tanto em sua resposta quanto em comunicações, é algo essencial durante um surto para que a população adote um comportamento protetor adequado à situação (Lim et al, 2020).…”
Section: Discussionunclassified